Decision making for anti-VEGF inhibitor continuation: dip stick? or urine protein/creatinine ratio? (VERSiON UP study) - Michio Nakamura; Taro Funakoshi; Shigeki Kataoka; Takahiro Horimatsu; Yoshitaka Nishikawa; Takeshi Matsubara; Takuro Mizukami; Tomoyuki Goto; Kenji Tsuchihashi; Eishi Baba; Takehiko Tsumura; Yoshiaki Mihara; et al. (BMC Cancer, 2022)
Abstract Background Monitoring proteinuria is important for the management of patients with cancer treated with anti-vascular endothelial growth factor (VEGF) or anti-VEGF receptor (VEGFR) inhibitors (VEGF/Ri). Here we investigated the difference between the urine protein/creatinine ratio (UPCR) and a qualitative value test (QV) on the decision making of treatment continuation and the usefulness of UPCR testing in patients with gastrointestinal cancer treated with anti-VEGF/Ri. Methods From January 2017 to December 2018, a survey was conducted based on the medical records of patients with gastrointestinal cancer with a QV of ≥2+ during the use of anti-VEGF/Ri at seven Japanese institutions participating in the Onco-nephrology Consortium. The primary endpoint was the ratio of the worst UPCR < 2.0 (low UPCR) in cases with a QV2+ at the point of the first proteinuria onset. The secondary endpoints were a comparison of low UPCR and worst UPCR ≥2.0 (high UPCR), the concordance rate between UPCR and QV in the Common Terminology Criteria for Adverse Events (CTCAE) grading, and the differences in the decision making for anti-VEGF/Ri continuation. Results Among the 71 patients enrolled, the proportion of low UPCR in onset QV2+ (n = 53) was 66% (n = 35). In a comparison between low (n = 36) and high UPCR cases (n = 24), body weight (P = 0.036), onset QV status (P = 0.0134), and worst QV status (P < 0.0001) were significantly associated with UPCR levels. The concordance rate for CTCAE Grade 2 of both the QV and UPCR was 83%. Regarding the judgment of anti-VEGF/Ri continuation, treatment was continued in 42.4% of cases when the QV became 3+, whereas only 25% continued treatment when the UPCR value became high. Conclusion Urine dipstick test results may overestimate proteinuria, and the UPCR result tended to be more critical than the QV when deciding the treatment policy. Trial registration This study is a multiple institutional retrospectively registered observational trial. Clinical Trial number: University Hospital Medical Information Network (UMIN) Clinical Trials Registry (protocol ID UMIN000042545 ).